After Le Monnier: Alessandro Manzoni’s contributions to copyright law - Traniello, Paolo (Bibliothecae.it, 2023)
The paper aims the influence that Alessandro Manzonim had on the drafting of law no. 2215 of 2 April 1865 on the legal regulation of the author’s right, even though the father of I promessi sposi had never personally taken part in parliamentary work.